The Relationship Between Patient Length of Stay and Family Anxiety Levels in the ICU - Dera Ariawan; Hadi Abdillah; Ernawati Hamidah; Hendri Hadiyanto (Jurnal Keperawatan Priority, 2025)
Anxiety is a common psychological response experienced by family members of patients treated in the Intensive Care Unit (ICU). The longer the duration of patient care, the greater the uncertainty and emotional burden that may be experienced by families. This study aims to determine the relationship between the length of patient hospitalization and the level of family anxiety in the ICU of RSUD Jampang Kulon. The research employed a quantitative correlational design with a cross-sectional approach. Data were collected from family members of patients treated in the ICU through a total sampling technique, with a sample size of 34 respondents. The Hospital Anxiety and Depression Scale (HADS) questionnaire was used to measure anxiety levels, and patient treatment duration was obtained from medical records. The results showed that most respondents experienced moderate to high levels of anxiety, with a tendency for increased anxiety corresponding to longer treatment durations. Statistical analysis using the Spearman Rank test indicated a significant relationship between the length of hospitalization and the level of family anxiety p-value = 0.001 (p-value < 0.05). The findings suggest that prolonged ICU care can elevate anxiety among family members, which may impact their psychological well-being and ability to support the patient. It is concluded that healthcare providers should consider implementing supportive interventions for families, especially when patient care in the ICU is extended, to help manage and reduce anxiety effectively.